AKTUALISASI NILAI-NILAI AL-QUR’AN TERHADAP FUNGSI PEMIMPIN DALAM KONSEP KEPEMIMPINAN ISLAM - Ismail Baharuddin (IAIN Padangsidimpuan, 2018)
Internalization and actualization of the values of the Al-Qur'an on the functions of a leader are considered not urgent, of course it is a group or group thought that does not understand Islam in a kaffah (comprehensive) manner. If we examine the Qur'an comprehensively, of course, it does not only study the faith and ubudiyah, but all aspects of life including those related to the functions and duties of leaders. Thus, the values and principles of leadership function contained in the Al-Qur'an must serve as the main guide in his leadership. The importance of the actualization of Al-Qur'an values for the function of a leader lies in the goal of human creation. Thus, it is considered important to actualize the values of the Al-Qur'an on the function of the leader in carrying out his functions and duties. Among the functions of a leader as hinted at in the Al-Qur'an are establishing prayers, welfare for the weak, cooperation in increasing faith, piety and good deeds, preventing munkar, upholding justice and truth, enforcing deliberation.